JALI-JALI CHICKEN ARANCINI SAUS AMBAL SEBAGAI FUSSION FOOD BERBASIS PANGAN LOKAL - Nani Ratnaningsih, Dian Siti Nurjanah (Prosiding Pendidikan Teknik Boga Busana, 2020)
High consumption of rice in Indonesia should be reduced by replacing it through substitution using jailjali seeds. In this research, it can be used in making appetizer foods, namely Jali-Jali Chicken Arancini Sauce Ambal. The purpose of this study was to obtain a b substitution recipe with jail-jali seeds, knowing the acceptability and nutritional value of making Jali-Jali Chicken Arancini Sauce Ambal. The research and development of this product uses Research and Development (R & D) research with a 4D model, namely (Define, Design, Develop, Disseminate). The panelists consisted of 30 semi-trained panelists and 80 untrained panelists. In the research of Jali-Jali Chicken Arancini Ambal Sauce with substitution of Jali-jali seeds as a food based fusion food appetizer can be accepted by the general public. This is based on the results of the T-Test that has been done by looking at the average yield of each product characteristic (color, aroma, texture, taste, overall). Keywords: jali-jali seeds, fussion food